Pengetahuan Tentang Menjaga Kebersihan Gigi Dan Mulut (Oral Hygiene) Pada Guru Di SDN Kertajaya 1 Surabaya Tahun 2023 - Desi Kurnia Puspitasari; Isnanto; Imam Sarwo Edi (SURABAYA DENTAL THERAPIST JOURNAL, 2024)
Introduction: Dental and oral health problems in children are an important concern in the development of children's health status, especially in school-age children. Problem: a problem in this study is the high percentage of class III students at SDN Kertajaya 1 Surabaya in the medium category. The purpose: This study is to know the knowledge about maintaining oral hygiene in teachers at SDN Kertajaya 1 Surabaya. Methods: This research is a descriptive study with the number of research targets as many as 25 teachers at SDN Kertajaya 1 Surabaya. Collecting research data using a questionnaire. The data analysis technique used in this study was to present and then presented in tabular form. Results: Based on the results of the study it was found that knowledge about how to brush teeth properly and correctly for teachers was in the less category, Knowledge about the frequency of brushing teeth for teachers was in the sufficient category, Knowledge about when to brush teeth for teachers was in the lacking category, and knowledge about food that could helpful and detrimental to dental and oral health in the good category. Conclusion: From this study it can be concluded that knowledge about maintaining oral hygiene for teachers at SDN Kertajaya 1 Surabaya obtained sufficient category results.